Impact of In-Pond Nursery of Shrimp (Penaeus monodon) Post Larvae on the Survival Rate and Production Under Modified Improved Culture System (Progressive Agriculture, 2013)
To observe the effectiveness of short time in-pond nursery of post larvae (PL) on the survival rate and production of shrimp (Penaeus monodon) under modified improved culture system, an experiment was conducted in earthen ponds at Brackishwater Station of Bangladesh Fisheries Research Institute, Khulna. Results of the experiment revealed that short time in-pond nursery of PL provided the significantly higher (p